PENGARUH PERPUTARAN TOTAL ASET, MANAJEMEN LABA, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2022-2024 - Ulyatur Roziqoh; Mohammad Yahya Arief; Nanda Widaninggar (Fakultas Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of Total asset turnover, Earnings management, and Leverage on Firm value with Profitability as an intervening variable in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. This study employed a quantitative research method using purposive sampling technique. The research sample consisted of 13 food and beverage sub-sector companies that met the research criteria. The data used were secondary data in the form of annual financial statements obtained from the official website of the Indonesia Stock Exchange (IDX). The data analysis method used Smart Partial Least Square (SmartPLS) 3.0.The results of the study indicate that Total asset turnover has a positive but insignificant effect on Profitability. Earnings management has a positive and significant effect on Profitability. Leverage has a negative and significant effect on Profitability. Total asset turnover has a positive and significant effect on Firm value. Earnings management, Leverage, and Profitability have positive but insignificant effects on Firm value. In addition, Profitability is unable to mediate the effect of Total asset turnover, Earnings management, and Leverage on Firm value.